Global health security and the health-security nexus: principles, politics and praxis - David McCoy; Stephen Roberts; Jonathan Kennedy; Salma Daoudi (BMJ Global Health)
The past four decades have seen a steady rise of references to ‘security’ by health academics, policy-makers and practitioners, particularly in relation to threats posed by infectious disease pandemics. Yet, despite an increasingly dominant health security discourse, the many different ways in which health and security issues and actors intersect have remained largely unassessed and unpacked in current critical global health scholarship. This paper discusses the emerging and growing health-security nexus in the wake of COVID-19 and the international focus on global health security. In recognising the contested and fluid concept of health security, this paper presents two contrasting approaches to health security: neocolonial health security and universal health security. Building from this analysis, we present a novel heuristic that delineates the multiple intersections and entanglements between health and security actors and agendas to broaden our conceptualisation of global health security configurations and practices and to highlight the potential for harmful unintended consequences, the erosion of global health norms and values, and the risk of health actors being co-opted by the security sector.